2018
DOI: 10.1167/iovs.17-23677
|View full text |Cite
|
Sign up to set email alerts
|

Automated Diagnosis and Grading of Diabetic Retinopathy Using Optical Coherence Tomography

Abstract: PurposeWe determine the feasibility and accuracy of a computer-assisted diagnostic (CAD) system to diagnose and grade nonproliferative diabetic retinopathy (NPDR) from optical coherence tomography (OCT) images.MethodsA cross-sectional, single-center study was done of type II diabetics who presented for routine screening and/or monitoring exams. Inclusion criteria were age 18 or older, diagnosis of diabetes mellitus type II, and clear media allowing for OCT imaging. Exclusion criteria were inability to image th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…17,18,19,20 Thanks to deep learning applications, it is possible to develop software with databases containing over 100,000 data points. 21,22 There are examples of studies using machine learning methods with fundus photographs, machine learning with OCT, and deep learning methods with OCT. 19,23,24,25,26,27 Some of these studies have reported nearly 100% sensitivity or specificity rates. 28,29…”
Section: Artificial Intelligence and Diabetic Retinopathymentioning
confidence: 99%
“…17,18,19,20 Thanks to deep learning applications, it is possible to develop software with databases containing over 100,000 data points. 21,22 There are examples of studies using machine learning methods with fundus photographs, machine learning with OCT, and deep learning methods with OCT. 19,23,24,25,26,27 Some of these studies have reported nearly 100% sensitivity or specificity rates. 28,29…”
Section: Artificial Intelligence and Diabetic Retinopathymentioning
confidence: 99%
“…Hence, accurate and early diagnosis of this disease can prevent the development of blindness. Detection of DR is done by examination of fundus and optical coherence tomography (OCT) images [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Finally they used deep fusion classification network (DFCN) to classify normal or diabetic regions. Sandhu et al [2] presented a novel CAD system that segments the retina into 12 layers and then some global features such as curvature, reflectivity, and thickness measured. Finally, a two-stage, deep network is used to classify normal and abnormal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Macular nonperfusion is a risk factor for disease progression, but patients are usually asymptomatic until advanced stages of disease ( 7 ). It is estimated that 38% of diabetics suffer from diabetic retinopathy ( 8 ).…”
Section: Introductionmentioning
confidence: 99%